2000
DOI: 10.1002/1096-8652(200008)64:4<306::aid-ajh12>3.0.co;2-v
|View full text |Cite
|
Sign up to set email alerts
|

Prolonged complete remission of myelodysplastic syndrome treated with danazol, retinoic acid and low-dose prednisone

Abstract: Myelodysplastic syndrome (MDS) is a diverse group of clonal hematologic neoplasms. Different medications have been tried in MDS; however, no effective treatment has been yet established. We report a patient with MDS who achieved a complete remission in response to combination therapy of danazol, retinoic acid, and prednisone. A 53-year-old female presented with pancytopenia, macrocytosis, and hypercellular bone marrow with erythroid hyperplasia and dysplasia and 10% ringed sideroblasts. Cytogenetic studies rev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…Danazol, a synthetic attenuated androgen, has been used widely for anemia in variety of disorders, including pure red cell aplasia, autoimmune hemolytic anemia, aplastic anemia, and IMF [9][10][11][12][13][14]. Cervantes et al [15] reported 30 IMF patients who took danazol for 20.5 months and 11 patients (37%) achieved complete remission (transfusion cessation with normal hemoglobin level).…”
Section: Discussionmentioning
confidence: 99%
“…Danazol, a synthetic attenuated androgen, has been used widely for anemia in variety of disorders, including pure red cell aplasia, autoimmune hemolytic anemia, aplastic anemia, and IMF [9][10][11][12][13][14]. Cervantes et al [15] reported 30 IMF patients who took danazol for 20.5 months and 11 patients (37%) achieved complete remission (transfusion cessation with normal hemoglobin level).…”
Section: Discussionmentioning
confidence: 99%
“…10,11 One study evaluating distinct molecular subtypes in pancreatic cancer that included 178 patients from The Cancer Genome Atlas found only 2 patients with BAGE2 deletions, which showed no correlation with exceptional response or favorable outcomes. 12 Our study highlights the importance of searching for biomarkers of response to identify smaller subsets of patients who experience exceptional responses not observed in the broader population. For example, the original trials of EGFR inhibitors in lung adenocarcinoma with no biomarker selection showed only modest activity, but once EGFR was identified as a predictive biomarker in a subset of patients, the true activity of these drugs became apparent.…”
Section: Original Researchmentioning
confidence: 92%
“…Although the patient might welcome such access, it could raise concerns among parents, caregivers, and guardians regarding the level of details visible to the patient. 12,13…”
Section: Disadvantages Of Patient Portal Accessmentioning
confidence: 99%
See 1 more Smart Citation
“…Danazol, the 2,3-isoxazol derivative of 17␣-ethynyl T, is a synthetic androgen and has been used for the treatment of endometriosis (8), mastopathy (9), myelodysplastic syndrome (10), and other diseases (11). Several pharmacological effects of danazol have been reported, including inhibition of gonadotropin release (12), competitive inhibition of steroidogenic enzymes (13), modulation of immunological function (14), and suppression of cell proliferation (15).…”
mentioning
confidence: 99%